2018
DOI: 10.3389/fphar.2018.01229
|View full text |Cite
|
Sign up to set email alerts
|

Do Corticosteroids Still Have a Place in the Treatment of Chronic Pain?

Abstract: Corticosteroids have played a standard role in the multimodal pain management in the treatment of chronic spinal pain (cervical and lumbar) and osteoarthritis pain over the past three decades. In this review we discuss different types of injectable steroids that are mainly used for injection into the epidural space (for the treatment of radicular back and neck pain), and as intra-articular injections for different types of osteoarthritis related pain conditions. Furthermore, we discuss different approaches tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
0
12
0
2
Order By: Relevance
“…Exposure to nucleus pulposus tissue is assumed to cause an auto-immune response leading to cytokine production and involvement of pro-inflammatory cells. Additionally, vertebral end plate devascularization may strengthen this response [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to nucleus pulposus tissue is assumed to cause an auto-immune response leading to cytokine production and involvement of pro-inflammatory cells. Additionally, vertebral end plate devascularization may strengthen this response [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is supported by many studies showing that corticosteroids have an immediate effect on pain by inhibiting the synthesis of proinflammatory cytokines that are released locally at the injury site [ 26 ]. For these reasons, corticosteroids, in association with local anaesthetics, are actually still considered as a treatment of choice in the pain management of chronic spinal pain (cervical and lumbar) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids have both direct and indirect roles, decreasing the production and release of multiple pro-inflammatory cytokines, and inhibiting phospholipase A2 and the arachidonic acid pathway (4,9,10). Steroids also inhibit the transcription of inflammatory genes, such as nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB), and, upon binding to glucocorticoid-responsive elements (GREs), can increase the production of anti-inflammatory genes (11).…”
Section: Introductionmentioning
confidence: 99%
“…The use of these injections has historically been controversial, and multiple studies have shown variable results, both supporting and discouraging this management (12)(13)(14)(15). However, as multiple studies associate steroids with higher pain relief scores compared with local anesthetics alone, there is an increasing interest in assessing this topic and promoting their use (7,11). To determine the real effect of epidural steroid injections (ESIs), researchers have focused not only on the types of drugs used but also on the other factors that affect their efficacy, such as the different existing injection approaches and the performance technique (4).…”
Section: Introductionmentioning
confidence: 99%